15.0k views
4 votes
Solve by completing the squareX^2 - 4x - 8 = 0

1 Answer

2 votes

The given expression is


x^2-4x-8=0

First, we divide the linear term by 2 and elevate it to the square power.


((4)/(2))^2=(2)^2=4

So, we have to add 4 on each side


\begin{gathered} x^2-4x+4=8+4 \\ x^2-4x+4=12 \end{gathered}

Then, we factor the trinomial given that is a perfect square trinomial, we take the square root of the first and third terms to express it as the square of a binomial


(x-2)^2=12

Now, we solve for x. First, we take the square root on each side


\begin{gathered} \sqrt[]{(x-2)^2}=\pm\sqrt[]{12} \\ x-2=\pm\sqrt[]{3\cdot4} \\ x=\pm2\sqrt[]{3}+2 \end{gathered}

Hence, the solutions are


\begin{gathered} x_1=2\sqrt[]{3}+2 \\ x_2=-2\sqrt[]{3}+2 \end{gathered}

User Pengyy
by
5.3k points